The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
https://uir.unisa.ac.za/handle/10500/23172
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.

Towards a suitable domestic arbitration process in Nigeria - Bamgbose, Ademola Jonathan (University of Warwick, 2016)
The Nigerian judicial system is currently in a state of distress. Not only has the judiciary been trailed by allegations of corruption, incompetence and god-fatherism amongst others, the wheels of justice in Nigeria are slowly grinding to a near halt. This is because of the large and growing case list of courts as well as the recurrent industrial strike actions embarked upon by court staff. As a solution to this crisis, stakeholders have put forward a number of suggestions, one of which is the use of alternative dispute resolution methods like domestic arbitration, as a solution to the problems of the judiciary and as a viable alternative to the court system. As we will however come to see in this thesis, Nigeria’s Arbitration and Conciliation Act 1988 (“Arbitration Act”), which is based on the UNCITRAL Model Law 1985, is not only outdated, it is also for many reasons not suitable and relevant to a developing country as Nigeria. For example, the existing Arbitration Act fails to take the legal and social idiosyncrasies of the Nigerian nation into consideration. Furthermore, the Act fails to incorporate the pre-existing and judicially recognized customary arbitration practice into the Act. In addition, the Nigerian Arbitration framework contains a number of anti-arbitration provisions, which have clearly inhibited the growth of domestic arbitration in Nigeria. Moreover, between 1988 and now, a number of beneficial changes have occurred within the sphere of arbitration and from which the Nigerian arbitration framework can draw lessons. All these among others, make the Nigerian Arbitration Act an unsuitable alternative to the court system in Nigeria. This thesis therefore recommends a bespoke domestic arbitration framework, which takes account of the legal and social idiosyncrasies of the Nigerian nation as well as recent but relevant domestic arbitration practices in similar jurisdictions as Nigeria. Among other recommendations, the proposed framework borrows a leaf from the deeply rooted and judicially recognised customary arbitration practice in Nigeria. Furthermore, in a bid to identify and incorporate relevant provisions and practices that have emerged within the sphere of domestic arbitration between 1988 and now, we undertake a comparative analysis of the Ghanaian Alternative Dispute Resolution Act 2010, the UNCITRAL Model Law 2006, the English Arbitration Act 1996 as well as the Uniform Act on Arbitration 1999 of OHADA. It is believed that this modern but tailored framework will encourage the use of domestic arbitration in Nigeria and by extension ameliorate the problems in the judicial system.
URI: http://webcat.warwick.ac.uk/record=b3059548~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (Administrative law); Ghana; Nigeria

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Enforceability of Arbitral Awards Containing Interest: A Comparative Study between Sharia Law and Positive Laws - Althabity, Mohammad M. (University of Stirling, 2016)
The dynamics of our globalised world open the way for international trade and transactions between different countries; this may lead to conflicts in laws where transactions and trade may be subject to different legal systems. One of the biggest issues in international commercial law is disputes over the charging of interest, for example with regard to late payment, interest-based loans, or compensation for damages. Interest disputes are considered to be a complex area of law and even more complex in the international field. At the international level, interest claims may be connected to many areas of commerce and thus governed by various laws, which are different from one country to another; moreover, each country has its own interest rate and such rates are changeable according to the nature of law and economics under some jurisdictions. Furthermore, the concept of interest itself is affected by influences such as religious beliefs and economic, political and cultural trends. Interest can be treated as a substantive or a procedural matter. The settlement of these disputes therefore faces difficulties. Arbitration, as a method for settlement of disputes, is characterised by special features that assist in resolving these issues; but it faces some obstructions, especially in international commercial arbitration. The practices of arbitral tribunals and national courts in this regard are different. The results of different interpretations, approaches, and theories with regard to arbitration, at the pre-arbitration, during arbitration and post-arbitration stages, may also differ widely due to the diversity of financial and legal systems such as Common Law, Civil Law and the Islamic legal system – Sharia Law – across different countries. Each legal system has a different methodology and theories, even within an individual country under one legal system, and a state within a federal system has its own laws, which may have different interpretations in this respect. The New York Convention of 1958 on enforcing foreign arbitral awards was established in favour of arbitral awards and for the purpose of unifying international rules of arbitration. This Convention provides some procedural and substantive rules for the enforcement of foreign arbitral awards, but also provides some grounds for refusal. These rules have been affected by different interpretations under different jurisdictions and legal systems, which lead to different perspectives on the matter of charging interest and settlement by arbitration. The outcome of applying the NYC under these interpretations often has the opposite of its intended effect: the rejection of foreign arbitral awards. Due to such ambiguities, courts occasionally intervene in arbitration in all its stages. The interventions of national courts occur in three stages: enforcement of the arbitration agreement, enforcement of the contract under the applicable law to the agreement, and enforcement of the foreign arbitral award. The confusion between substantive and procedural laws also creates confusion with respect to public policy, non-arbitrability and enforceability. In addition, there may be a lack of clarity on the scope of arbitration with respect to the parties’ agreement, whether or not the parties have agreed to the interest rates and periods and whether or not they have agreed to the authority of the arbitrator. These issues affect the enforceability of an arbitration agreement, the law applicable to the disputed contract, the freedom of parties, the authority of the arbitrators and the enforceability of the awarded interest. The thesis studies how arbitral awards containing interest have been interpreted across the three aforementioned legal systems under the NYC 1958 in Saudi Arabia, Egypt, the UAE, England, France, and the US and the enforceability of such awards.
https://dspace.stir.ac.uk/bitstream/1893/23090/1/Enforceability%20of%20Arbitral%20Awards%20Containing%20Interest.pdf
Keywords: Arbitrage; Arbitral award enforcement; Arbitration; Chari'a law; Sentence arbitrale; Sharia Law

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
URI: https://repository.up.ac.za/handle/2263/60060
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa

A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

'You wouldn't steal a car' vs 'information wants to be free' : regulatory failure of copyright law through the prism of systems theory - Gracz, Katarzyna (European University Institute, 2016)
The thesis aims at explaining current regulatory crisis of copyright law (understood as its inability to regulate social dynamics as regards production, reproduction, dissemination of and access to information goods) through the application of systems theory. It refers to the concept of autopoietic legal system in order to draft a model representing the ecosystem in which copyright law functions. This model not only allows for observing copyright regime as it stands currently but also for analysing how it evolved over time. It scrutinises the interdependencies between the legal system and other constituent elements of its ecosystem: politics, economy, art, science, technology, religion, mass media, education as well as non-functionally differentiated segments of society: circles of relatives and friends. The main goal of this analysis is to highlight the fact that the current regulatory crisis of copyright is the result of the legal system's failure to equally acknowledge all the diverse rationalities constituting its ecosystem. The primary hypothesis of the study is that the core of the problem may be attributed to the divergence between legal norms, and competing non-legal copynorms constructed in the process of co-evolution within various elements of the model in question. In the analysis all the relevant copynorms understood as segmented social norms regulating social dynamics with respect to production, reproduction, dissemination of and access to information goods have been reconstructed to indicate their potential to oppose legal regulations. The thesis pivots around the concept of reflexive justice which refers to the equal acknowledgement of colliding rationalities. It concludes with the firm statement that copyright law in the digital environment needs profound reform. The concept of reflexive justice as developed within the systems theoretical approach is perceived by the author of this thesis as the most promising starting point for the new philosophy of copyright law.
Accepted: 2016-05-17T13:43:06Z
Keywords: Copyright; Intellectual property; Sociological jurisprudence

Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade

Remedies for passengers for flight delays caused by force majeure - Ko, Li-Juan (McGill University, 2016)
This thesis intends to justify the necessity to propose an alternative remedy mechanism to current air carriers' obligations in offering complimentary services to passengers in force majeure delays. This mechanism mitigates disputes arising from passengers' dissatisfaction with air carriers' services. The proposal is the result of extensive research arising from a fundamental question: Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure? The source of information for this thesis stems from a combination of the analysis of case law and statutes on one hand, and experience drawn from professional practice and cultural context on the other. This thesis discusses the intersection of international conventions, national legislation, and the practice and expectations of air carriers and their passengers. The thesis specifically examines and highlights the inadequacies of relying on existing international conventions to provide a harmonized solution for flight delay claims. In terms of national remedy mechanisms, research and analysis have been focused on the advanced aviation markets in the West, such as the US and the EU, and on the emerging markets in the East, such as Mainland China and Taiwan. The research and analyses reveal how national laws, which are deeply influenced by socio-economic, political and cultural factors, trigger distinct conflicts of interest between air carriers and passengers. During the course of reviewing the legal jigsaw and uncertainties in current legal practice, the findings revealed more issues. In brief, making more laws cannot guarantee an effective solution for flight delay claims, especially in different jurisdictions. Accordingly, the findings support that a novel solution, free from the uncertainties and complexities in the current legal framework, is needed to resolve passengers' claims or expectations resulting from force majeure delays. Essentially, this novel solution is to form an alternative remedy mechanism that includes a fund and codes of conduct. The fund will implement a risk-sharing function among stakeholders that will include passengers, air carriers and airport managing entities. To mitigate disputes, the proposed codes of conduct will include guidelines to operate the fund with the aim of mutual respect between passengers and air carriers. In so doing, the remedy mechanism will provide equitable answers to the question: "Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure?"
Identifier: https://escholarship.mcgill.ca/concern/theses/fn1071806
Keywords: Air carriers' obligation; Alternative remedy; Flight delay; Force majeure; Remedies

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Developing efficient dispute resolution solutions for international commercial disputes: ways to address concerns associated with the combined use of mediation and arbitration by the same neutral - Nigmatullina, Dilyara (The University of Western Australia, 2016)
Securing fast, inexpensive and enforceable redress is vital for the development of international commerce. In a changing international commercial dispute resolution landscape, the combined use of mediation and arbitration, and particularly a combination where the same neutral acts as a mediator and an arbitrator (same neutral (arb)-med-arb), has emerged as a dispute resolution approach offering these benefits. However, to date there has been little agreement on several aspects of the combined use of processes, which the literature often explains by reference to the practitioner’s legal culture. There is a heated debate in the international dispute resolution community as to whether it is appropriate for the same neutral to conduct both mediation and arbitration. When the same neutral acts as a mediator and an arbitrator, caucuses become a primary concern. This is largely due to the danger that an arbitrator will appear to be, or actually be biased, and the risk that the process may offend the principles of due process.A review of the literature shows that the combined use of mediation and arbitration raises more questions and concerns than it offers answers and solutions. This thesis proposes remedies for this situation. The purpose of this thesis is twofold. First, to investigate ways to address concerns associated with the same neutral (arb)-med-arb, which should allow parties to benefit from time and cost efficiencies of the process and the ability to obtain an internationally enforceable result. Second, to examine whether the perception and use of the same neutral (arb)-med-arb varies depending on the practitioner’s legal culture. The research involved an analysis of legal sources complemented by a two stage empirical study conducted through questionnaire and interview.The thesis identifies three major ways to address concerns associated with the same neutral (arb)-med-arb: 1) the involvement of different neutrals in combinations, 2) procedural modifications of the same neutral (arb)-med-arb, and 3) the implementation of safeguards for using the same neutral (arb)-med-arb. It demonstrates that not all of these ways will achieve the goals of fast, inexpensive and enforceable dispute resolution. The results support the conclusion that the perception and use of the same neutral (arb)-med-arb varies throughout the world depending on the practitioner’s legal culture. This and other factors ultimately affect the choice of ways to address concerns associated with the same neutral (arb)-med-arb. Further to these significant results, the thesis argues that the same neutral (arb)-med-arb is not a ‘one-size-fits-all’ process. Other combinations discussed in the thesis require more attention from practitioners and academics.This thesis makes a substantial and original contribution to the understanding of combinations in international commercial dispute resolution in four ways. First, the empirical study is the first study to investigate specifically the use of combinations in international commercial dispute resolution. Its results shed light on the use of combinations in international commercial dispute resolution, their common triggers, the way in which the processes are combined most frequently, and the most common forms of recording the outcome of combinations. Second, the thesis synthesises existing ways of addressing concerns associated with the same neutral (arb)-med-arb in international commercial dispute resolution and groups them into the three major categories mentioned above. Third, having identified that there is scope for a more widespread use of combinations in international commercial dispute resolution, the thesis provides recommendations on how to enhance the use of combinations. Finally, the thesis highlights several areas where future research is needed.
https://research-repository.uwa.edu.au/en/publications/developing-efficient-dispute-resolution-solutions-for-internation The UWA Profiles and Research Repository
Keywords: Arbitrage; Arbitragem; Arbitration; Combined processes; Commercial; Dispute resolution (Law); International; Legal culture; MARD; Mediación; Mediation; Mediação; Médiation; Same neutral

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

Water as public property : a parallel evaluation of South African and German law - Viljoen, Germarié (North-West University, 2016)
With the introduction of the National Water Act 36 of 1998 (NWA) in South Africa’s water regulatory regime, the foundations of the country’s existing water law system changed fundamentally. The NWA was promulgated with the primary aim to reform the law relating to water resources. The preamble to the NWA states that water is “a scarce natural resource that belongs to all people.” Section 3 of the NWA continues along similar lines and stipulates that all water use rights fall under the centralised control of the state or public trustee to inter alia improve the distribution, management, use, conservation and equality of access to this scarce resource. Statutory transformation of this nature has inevitable and important legal implications. It has for example been argued that the changed system has brought about a reallocation and redefinition of property rights to natural resources; a transformation which will inevitably impact the nature, form, extent, limits and protection of access and use rights that can be acquired in water as a natural resource. In an effort to understand the extent of the legal transformation brought about by the concept of public trusteeship, this thesis considers the impact of the concept in the broader South African water law context. The concept of public trusteeship is a novel concept in South African jurisprudence, without established links to existing principles of law. This thesis subsequently focuses on how and to what extent the German property law concept of őffentliche Sache may inform the development and interpretation of the South African concept of public trusteeship as entrenched in the NWA. Consequently, this thesis commences with an exposition of information on the idea of property and the relevance and importance of the different property rights regimes against which both the South African and German property regimes can be evaluated. This is followed by a description of the South African property rights paradigm and its different property concepts. The research introduces a novel take on the discussion of the regulation of rights in natural resources in South Africa, namely a “stewardship ethic of public trusteeship”. As a stewardship ethic could potentially influence the regulation of property in natural resources and even perhaps the property regime within which water as natural resource is regulated in South Africa, the next section of the research proceeds with a historical account of the South African water law dispensation. Although the historical review indicates that the concept of public trusteeship is not part of South Africa’s common law heritage, some of its principles find application in the common law concept of res publicae. The conclusion is that the concept of public trusteeship does not merely (re-) introduce the res publicae concept into the South African water realm. The concept of public trusteeship is a novel concept that was statutorily introduced into the South African water regulatory framework in terms whereof “ownership” of water resources vests in the national government, and are consequently administered on behalf of the nation and generations yet to come. A separate section of the research analyses and contextualises the concept of őffentliche Sache as it functions in German law to offer new insight into the implications that the statutorily introduced concept of public trusteeship might have on water as property and the property regime within which water is regulated in South Africa. This guides the study to the next section of the research, which illustrates that the concept of őffentliche Sache is at the basis of the German water regulatory framework. The conclusion of the study proposes an understanding of the concept of public trusteeship in South Africa based on lessons learned from the German concept of őffentliche Sache.
Keywords: Constitutional property; German water regulatory framework; National Water Act; Property; Property rights regime; Public property; Public trusteeship; Res publicae; Water rights; Öffentliche Sache